Discussing the faith multilingual and metalinguistic conversations about religion - Sauer Bredvik, Linda (Diskursmuster ;, 2020)
Encounters between people of diverse religious faiths and worldviews are becoming more common in an increasingly globalized and mobile world. Research has not, however, kept pace by investigating how people talk about their faith with others who believe differently. This monograph addresses that deficit by taking an emergent path, combining qualitative and quantitative analysis to investigate and understand multilingual speakers' discursive behaviors in multiparty interreligious dialogues. Using 33 hours of recordings from conversations across seven research sites, Sauer Bredvik investigates how speakers' multilanguaging practices interact with other indexical and referential signs (unfilled pauses, disfluency, pragmatic markers) to affect how constitute messages are understood. By combining corpus-assisted discourse analysis with emic data taken from observation and 11 hours of participant interviews, one is able to identify distinct patterns of use between these metalinguistic indicators and a dialogue outcome. Readers will gain an understanding of how people of various linguistic and faith backgrounds use all their semiotic resources to display hospitality and respect for the Other in multilingual, multifaith settings.